The body in balance : humoral medicines in practice - Horden, Peregrine; Hsu, Elisabeth (Epistemologies of healing, 2013)
"Focusing on practice more than theory, this collection offers new perspectives for studying the so-called "humoral medical traditions," as they have flourished around the globe during the last 2,000 years. Exploring notions of "balance" in medical cultures across Eurasia, Africa and the Americas, from antiquity to the present, the volume revisits "harmony" and "holism" as main characteristics of those traditions. It foregrounds a dynamic notion of balance and asks how balance is defined or conceptualized, by whom, for whom and in what circumstances. Balance need not connote egalitarianism or equilibrium. Rather, it alludes to morals of self care exercised in place of excessiveness and indulgences after long periods of a life in dearth. As the moral becomes visceral, the question arises: what constitutes the visceral in a body that is in constant flux and flow? How far, and in what ways, are there fundamental properties or constituents in those bodies?"--